Compact and Broadband Substrate Integrated Dielectric Resonator Antenna Suitable for 5G Millimeter-Wave Communications - Jie-Er Zhang; Qinfang Zhang; Wei Qin; Wen-Wen Yang; Jian-Xin Chen (IEEE Open Journal of Antennas and Propagation, 2023)
To date, few broadband DRAs can cover n257, n258, n260, and n261 bands with a small physical footprint (e.g., < $0.4λ _{0}× 0.4λ _{0}× 0.15λ _{0}$ , where $λ _{0}$ is the free-space wavelength at 28GHz). This article proposes a compact and broadband substrate-integrated dielectric resonator antenna (SIDRA) suitable for 5G millimeter-wave band applications. Four operating modes from three resonators, including TE111 and TE131 modes from the DR, slot mode from the H-shaped feeding slot, and patch mode from the inserted ring patch, are excited to achieve a bandwidth of 61.9% (24-45.5 GHz) with a compact size of $0.37{λ }_{0}× 0.37{λ }_{0}× 0.125{λ }_{0}$ . The proposed DRA can be extended to an array with $\sim 0.5 λ _{0}$ element interval to obtain wide-angle beam scanning capability. A $1× 4$ SIDRA array was simulated, achieving beam-scanning area of ±45° and ±32° at the frequencies of 28/39 GHz. Further, the DRA array was fabricated and tested. It offers a measured 10-dB bandwidth (|S11| ≤ −10 dB) of ~60.4% (23.5-43.7 GHz), in which the gain varies between 10.1 to 12.5 dBi.